This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
did the same!
We note that as x → 0 , sin ( π cos 2 x ) → 0 and x 2 → 0 . So this is a 0/0 case and we can use the L'Hôpital's rule as follows.
L = x → 0 lim x 2 sin ( π cos 2 x ) = x → 0 lim 2 x cos ( π cos 2 x ) ( − 2 π cos x sin x ) = x → 0 lim 2 − sin ( π cos 2 x ) ( π 2 sin 2 2 x ) + cos ( π cos 2 x ) ( − 2 π cos 2 x ) = 2 0 + cos ( π ( 1 ) ) ( − 2 π ( 1 ) ) = π Differentiate up and down w.r.t. x Still 0/0, differentiate again
Very nice solution!
Wounderfull
Problem Loading...
Note Loading...
Set Loading...